NILAI MUATAN TITIK NOL (MTN) DAN HUBUNGANNYA DENGAN ERAPAN KALIUM PADA TANAH GAM BUT PANTAI JAMBI DAN KALIMANTAN TENGAH - R. Purnamayani; Supiandi Sabiham; Sudarsono .; L. K. Darusman (Jurnal Ilmu Tanah dan Lingkungan, 2004)
One of the important chemical aspects of peatland management which has not been paid attention to is Zero Point of Charge (ZPC). By determining soil ZPC value, the sorption and bounding of cations can be estimated in certain pH.value. Low of Potassium (K) is one of the other problems of peatland This nutrient is easily leaching from peat because of the weakness bounding. This research is aimed to determine ZPC value and maximum sorption of K of the coastal peats of Jambi and Central Kalimantan with decomposition degrees of sap ric, hemic, and fabric. The location of this research is in Soil Chemical and Fertility Laboratory, Department of Soil Science, Faculty of Agriculture IPB Bogor, from September 2000 - March 2001. Soil samples were taken from two areas, Lagan (Jambi) and Samuda (Central Kalimantan). The determinations of K maximum sorption was carried out on 4 pH level as treatments (0.25 point below and above pHZPC. 0.50 point above pHZPC and at pHZPC. It was concluded that ZPC value of coastal peats of Jambi with decomposition degrees of sapric was 5.01, decomposition degrees of hemic was 4.13, and decomposition degrees of fibric was 4.56, while coastal peats of Central Kalimantan with decomposition degrees of sapric was 4.25, decomposition degrees of hemic was 4.28, and decomposition degrees of fibric was 4.48. Jambi peat with sapric decomposition level has the lowest K maximum sorption at Zpc. In contrast, Central Kalimantan peat with sapric decomposition level has the highest K maximum sorption. Keywords: Peat, potassium, sorption, ZPC